Analisis Program Full day Terhadap Semangat Belajar Siswa di Sekolah Dasar Islam Terpadu (SDIT) - Tegu Reski Amanah; Murniyetti Murniyetti; Nurjanah Nurjanah (An-Nuha, 2023)
This research is backgrounded with the transformation and development of the education system in Indonesia which has begun to implement a lot of education systems throughout the day or what is called a full day school program. This research uses a descriptive qualitative method, the object of this study is students of the Integrated Islamic Elementary School (SDIT) Nurul Ikhlas Padang and the subject of this study is the student's enthusiasm for learning. Then the data obtained from the results of observations, interviews with informants, and documentation to see the existing phenomena. The results of this study show how the form of the Nurul Ikhlas Padang Integrated Islamic Elementary School (SDIT) full-day program has followed national education standards. What are the advantages and disadvantages of implementing the Nurul Ikhlas Padang Integrated Islamic Elementary School (SDIT) full-day program. How are the supporting and inhibiting factors in the implementation of the full day program and its impact on the enthusiasm for student learning at the Nurul Ikhlas Padang Integrated Islamic Elementary School (SDIT).